Künstliche Intelligenz in der Medizin: Einsatzgebiete, zugelassene Produkte und Trends = Artificial Intelligence in Medicine: Application Areas, Approved Products, and Trends - Heimann, Tobias (Zeitschrift für medizinische Ethik, 2025)
AbstractArtificial intelligence (AI) has rapidly evolved in medicine and is now clinically established across various domains. This article provides a practice-oriented overview of AI applications in imaging, radiology, radiation therapy, and other specialties. Using concrete examples, it highlights use cases, benefits, and challenges. The focus is on approved products and their integration into clinical workflows. The aim is to illustrate the potential of AI to enhance patient care., AbstractArtificial intelligence (AI) has rapidly evolved in medicine and is now clinically established across various domains. This article provides a practice-oriented overview of AI applications in imaging, radiology, radiation therapy, and other specialties. Using concrete examples, it highlights use cases, benefits, and challenges. The focus is on approved products and their integration into clinical workflows. The aim is to illustrate the potential of AI to enhance patient care.